PERAN DPRD KABUPATEN KUTAI KARTANEGARA DALAM PELAKSANAAN FUNGSI PEMBENTUKAN PERATURAN DAERAH (STUDI TENTANG PELAKSANAAN HAK INISIATIF DPRD PRIODE 2014-2019) - Salehuddin Salehuddin (Jurnal Paradigma (JP), 2021)
This article will describe and analyze the role of the Kutai Kartanegara DPRD in carrying out the function of forming Regional Regulations. This research is a descriptive study using a qualitative approach and data analysis using an interactive model. The results showed that the Kutai Kartanegara DPRD for the 2014-2019 period played a role in carrying out the function of forming regional regulations in accordance with the provisions of Law No. 23 of 2014, Permendagri No. 80 of 2015, and DPRD Standing Orders Number 1 of 2016 but not maximally in completing the target of the Regional Regulation Formation Program that has been agreed with the Regional Government every yearKeywords: Role, DPRD, Regional Regulation